1995
DOI: 10.1155/1995/293905
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Temporal Lobe Damage and the Partial Kluver–Bucy Syndrome

Abstract: The characteristic behavioural constellation of Kluver-Bucy syndrome is believed to be diagnostic of bilateral temporal lobe damage, even in the partial syndrome. The case described is that of a 54 year old woman with gross atrophy of her right temporal lobe following neurosurgery who developed hyperphagia (with driven food-seeking behaviour), placidity and hyposexuality. Her case thereby meets criteria for the partial syndrome but without evidence of bilateral damage. The discussion covers the various present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In an early study, Downer (1961) demonstrated that unilateral amygdala lesions in a split-brain monkey were capable of producing a Kliiver-Bucy syndrome but only in reaction to visual stimuli when visual input was restricted to the hemisphere ipsilateral to the lesion. More recently, rare cases of full (Ghika-Schmid, Assal, DeTribolet, & Regli, 1995) and partial (Bates & Sturman, 1995) Kltiver-Bucy syndrome in humans with unilateral temporal lobe damage have been reported.…”
Section: Values Represent Group Means (+ Sem) Amentioning
confidence: 99%
“…In an early study, Downer (1961) demonstrated that unilateral amygdala lesions in a split-brain monkey were capable of producing a Kliiver-Bucy syndrome but only in reaction to visual stimuli when visual input was restricted to the hemisphere ipsilateral to the lesion. More recently, rare cases of full (Ghika-Schmid, Assal, DeTribolet, & Regli, 1995) and partial (Bates & Sturman, 1995) Kltiver-Bucy syndrome in humans with unilateral temporal lobe damage have been reported.…”
Section: Values Represent Group Means (+ Sem) Amentioning
confidence: 99%
“…The selective decline in the PIQ, the mild episodic visual memory deficits, difficulties on visuomotor tracking tasks, and aprosody could be considered as posttraumatic neuropsychological sequels, and could be explained with predominant posttraumatic right hemispheric lesion [5,9]. Organic hyperphagia is an uncommon condition that occurs in KLS, Kluver-Bucy syndrome, Prader-Willi syndrome, hypothalamic and, occasionally, in thalamic lesions [1]. The human Kluver-Bucy syndrome has been divided into six component symptoms: visual agnosia, placidity, altered sexual behavior, hyperorality, altered dietary habits (the only symptom from this group undoubtedly present in our patient) and hypermetamorphosis, and a minimum of three of these symptoms was required for the diagnosis of the partial form of this syndrome [13].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the partial syndrome, the characteristic behavior cluster of the Kluver-Bucy syndrome was thought to be diagnostic of bilateral temporal damage. However, Bates and Sturman [1] reported a woman with hyperphagia, placidity and hyposexuality associated with gross atrophy of her right temporal lobe following neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…37 Dietary restriction and practical approaches like the use of refrigerator locks are the most obvious interventions but not always possible. The resulting weight gain causes additional morbidity and even mortality.…”
Section: Feeding Disordersmentioning
confidence: 99%
“…The resulting weight gain causes additional morbidity and even mortality. 37 Dietary restriction and practical approaches like the use of refrigerator locks are the most obvious interventions but not always possible. There is only a case report literature to guide the clinician in this challenging area.…”
Section: Feeding Disordersmentioning
confidence: 99%